“Diamonds are a girl’s best friend”? Tracing the implications of a song in Cathy Yan’s Birds of Prey (and the Fantabulous Emancipation of One Harley Quinn) - Clarke K (My University)
When Harley Quinn (Margot Robbie) dressed as Lorelei (Marilyn Monroe) from 1953 film Gentlemen Prefer Blondes performs “Diamonds are a Girl’s Best Friend” in Cathy Yan’s 2020 film Birds of Prey (and the Fantabulous Emancipation of One Harley Quinn), links are drawn between 70 years of film history and women’s representation on screen. In this article, I put various iterations of “Diamonds” into dialogue to explore how this moment in Birds of Prey might be understood. I consider this scene as central to understanding Quinn’s “emancipation,” with the representation of women’s security and control over their lives key themes in the history of this scene. The return to this song throughout the histories of film and video enables a sense of solidarity across time, acknowledging the systemic problems that remain unresolved, and contemplation of this can alter the ways we understand characters and texts, past, present, and future.
(c) The Author/s
Keywords: 1699 Other Studies in Human Society; 2001 Communication and Media Studies